2018
DOI: 10.1016/j.dib.2018.04.076
|View full text |Cite
|
Sign up to set email alerts
|

Data on fantasy vs contact driven internet-initiated sexual offences: Study selection, appraisal and characteristics

Abstract: Data presented within this article supports the findings of the manuscript “A systematic review of fantasy driven vs contact driven internet-initiated sexual offences: Discrete or overlapping typologies?” (Broome et al., in press) [1]. Inclusion and Exclusion criteria of study selection, PICO Formulation of Study Appraisal, as well as the Study Characteristics and Methodology of included studies are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Further Broome et al (2018aBroome et al ( , 2018b found that adults with both online and offline sexual intentions attempted to build a relationship with victims. This, along with the results of the present study, suggests that whilst the implicit goal may be sex, a key feature of the interaction is the development of a relationship; much like the development of a sexual relationship between two adults.…”
Section: Discussionmentioning
confidence: 99%
“…Further Broome et al (2018aBroome et al ( , 2018b found that adults with both online and offline sexual intentions attempted to build a relationship with victims. This, along with the results of the present study, suggests that whilst the implicit goal may be sex, a key feature of the interaction is the development of a relationship; much like the development of a sexual relationship between two adults.…”
Section: Discussionmentioning
confidence: 99%